THE IMPACT OF NEGATIVE ONLINE CONSUMER REVIEW AND BRAND AWARENESS ON POTENTIAL CONSUMER PURCHASE INTENTION AT PRUDENTIAL INSURANCE COMPANY IN MANADO - Angelia Theresia Mandagi; David P. E. Saerang; Ferdinand J Tumewu (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
Negative online consumer review and brand awareness plays an important role on potential consumer purchase intention. Negative online consumer review fades overtime but the increasing of the brand awareness remind the same and potential consumer tends to buy familiar and well-known product. This research examines the Impact of Negative Online Consumer Review and Brand Awareness on Potential Consumer Purchase Intention at Prudential Insurance Company in Manado. This research are using Quantitative Research Method with 100 samples and using Questionnaire data collection technique, Negative Online Consumer Review and Brand Awareness stimultaneously have positive and significant effect toward the Potential Consumer Purchase Intention at Prudential Insurance in Manado. Prudential needs to pay more attention to all the negative online consumer review and the right way in responding to negative online consumer review is needed to increase their potential consumer purchase intention